Secretion by Pseudomonas aeruginosa: fate of a cloned gram-positive lipoprotein deletion mutant. - Nielsen, J B (1983)
In gram-positive organisms, glyceride-cysteine thioether lipoproteins are frequently associated with secretion. They constitute membrane-bound forms retained by the cell but releasable late in growth phase. Most gram-negative organisms secrete very few proteins to the culture fluid; thioether lipoproteins in such organisms, typified by the enteric bacterium Escherichia coli, are integral outer membrane components for the most part. Unusual among gram-negative organisms, however, are Pseudomonas strains, known for extracellular export of a number of proteins. To examine whether a fundamental difference exists between the processing of lipoproteins in Pseudomonas strains and in nonsecretory gram-negative organisms, we examined the fate in Pseudomonas aeruginosa and E. coli of a cloned gram-positive secretory lipoprotein, Bacillus licheniformis penicillinase. A nonlipoprotein deletion mutant of the same gene was also examined in P. aeruginosa, and its processing was compared with that in E. coli. No important differences were found between P. aeruginosa and E. coli for either the lipoprotein or its deletion mutant. Thus, the contrast in secretory abilities of the two organisms does not appear to result from a difference in their general secretory systems.